THE USE OF AUTHENTIC MATERIALS IN TEACHING ENGLISH AS A FOREIGN LANGUAGE - Shamsuddinova Diyoraxon Yorqinbek qizi; Mirzaazizova Farangiz (TADQIQOTLAR, 2025)
Abstract The integration of authentic materials in English as a Foreign Language (EFL) classrooms has garnered significant attention for its potential to enhance language acquisition. Authentic materials—resources created for native speakers—offer learners exposure to real-life language use, cultural nuances, and contextualized communication. This article examines the benefits and challenges of employing authentic materials in EFL instruction, drawing on recent studies and pedagogical insights. It also provides practical strategies for effective implementation, aiming to guide educators in enriching their teaching practices and fostering learners’ communicative competence.